Challenges of Real-World Materials in English Language Learning - Tursunov Shohruhbek Sherzod o’g’li; Ziyodullayev Jamshid Azamat o’gli (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
This article critically examines the challenges of using authentic materials in language classrooms. While real-world resources offer valuable exposure to natural language, they often present difficulties related to level appropriateness, length, cultural bias, and linguistic complexity. Drawing on scholarly perspectives, the study highlights the need for careful selection to ensure effective and meaningful learning outcomes.